Long-Term Mortality After TAVI for Bicuspid vs. Tricuspid Aortic Stenosis: A Propensity-Matched Multicentre Cohort Study - Gasecka, Aleksandra; Walczewski, Michał; Witkowski, Adam; Dabrowski, Maciej; Huczek, Zenon; Wilimski, Radosław; Ochała, Andrzej; Parma, Radosław; Scisło, Piotr; Rymuza, Bartosz; Zbroński, Karol; Szwed, Piotr; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Patients with bicuspid aortic valve (BAV) stenosis were excluded from the pivotal trials of transcatheter aortic valve implantation (TAVI). We compared the in-hospital and long-term outcomes between patients undergoing TAVI for bicuspid and tricuspid aortic valve (TAV) stenosis. Methods: We conducted a retrospective registry-based analysis including patients undergoing TAVI for BAV and TAV at 5 centres between January 2009 and August 2017. Primary outcome was long-term all-cause mortality. Secondary outcomes were in-hospital mortality, procedural complications and valve performance. Results: Of 1,451 consecutive patients who underwent TAVI, two propensity-matched cohorts including 130 patients with BAV and 390 patients with TAV were analysed. All-cause mortality was comparable in both groups up to 10 years following TAVI (HR 1.09, 95% CI: 0.77-1.51). Device success and in-hospital mortality were comparable between the groups (96% vs. 95%, p=0.554 and 2.3% vs 2.1%, p=0.863, respectively). Incidence of procedural complications was similar in both groups, with a trend towards higher rate of stroke in BAV patients (5% vs 2%, p=0.078). Incidence of moderate or severe paravalvular leak (PVL) at discharge was comparable in both groups (2% vs 2%, p=0.846). Among BAV patients, all-cause mortality was similar in self-expanding and balloon-expandable prostheses (HR 1.02, 95% CI: 0.52-1.99) and lower in new-generation devices, compared to old-generation valves (HR 0.27, 95% CI 0.12-0.62). Conclusions: Patients who had undergone TAVI for BAV had comparable mortality to patients with TAV during 10 years after the procedure. The device success, in-hospital mortality, procedural complications and PVL rate were comparable between the groups.